DIARRHEA POISONING AND COURSE IN PATIENTS, TREATMENT METHODS - Khazhimatov Ravshanbek Sobirzhanovich (Scholar Express Journals, 2023)
The main causes of acute diarrhea are infection and malnutrition. Acute diarrhea is also associated with the consumption of food (seafood) stored in unhygienic conditions or contaminated during irrigation.
Keywords: conditions; contaminated; infection; diarrhea